Examining the exploitation of vulnerable migrant populations and interventions to combat human trafficking and modern-day slavery within the illegal UK cannabis cultivation industry - Holly Necchi; Tracy Bradford (Journal of Economic Criminology)
The illegal cultivation of cannabis in the UK is a serious problem that can involve the exploitation of vulnerable migrant populations who are trafficked to work as cannabis growers under conditions of debt bondage and modern slavery. Although there is much public interest in modern slavery and human trafficking (MSHT), the prominent focus is on child criminal exploitation and sexual exploitation. The lived experiences and perspectives of cannabis growers and the trauma these victims endure, as well as the methods of control and coercion used by the perpetrators, is under-researched. By scoping the existing literature, the following issues are explored: The vulnerability of migrants is shaped by multiple factors, such as poverty, inequality, and lack of legal status. The perpetrators use various methods of control and coercion, such as deception, threats, violence, and debt manipulation. The victims suffer from physical and psychological trauma, such as injuries, illnesses, anxiety, depression, and fear. Finally, there is evidence that protective legislation and the actions of the criminal justice system in some MSHT cases are inadequate, resulting in the criminalisation of cannabis growers, rather than on their protection and support as victims of human rights violations. The findings suggest a significant need for improving the identification, referral, and protection of cannabis growers who are victims of MSHT. This requires addressing the research gaps identified in this review, enhancing the training and understanding of MSHT and non-punishment provisions amongst criminal justice workers, and adopting a holistic approach to victim support.